Current challenges in providing good leukapheresis products for manufacturing of CAR-T cells for patients with relapsed/refractory NHL or ALL - Korell, Felix; Sauer, Sandra; Veelken, Kaya; Hennemann, Hannah Mai; Schubert, Maria-Luisa; Sauer, Tim; Müller-Tidow, Carsten; Dreger, Peter; Schmitt, Michael; Schmitt, Anita (Cells, 2020)
Background: T lymphocyte collection through leukapheresis is an essential step for chimeric antigen receptor T (CAR-T) cell therapy. Timing of apheresis is challenging in heavily pretreated patients who suffer from rapid progressive disease and receive T cell impairing medication. Methods: A total of 75 unstimulated leukaphereses were analyzed including 45 aphereses in patients and 30 in healthy donors. Thereof, 41 adult patients with Non-Hodgkin’s lymphoma (85%) or acute lymphoblastic leukemia (15%) underwent leukapheresis for CAR-T cell production. Results: Sufficient lymphocytes were harvested from all patients even from those with low peripheral lymphocyte counts of 0.18/nL. Only four patients required a second leukapheresis session. Leukapheresis products contained a median of 98 × 108 (9 - 341 × 108) total nucleated cells (TNC) with 38 × 108 (4 - 232 × 108) CD3+ T cells. Leukapheresis products from healthy donors as well as from patients in complete remission were characterized by high TNC and CD3+ T lymphocyte counts. CAR-T cell products could be manufactured for all but one patient. Conclusions: Sufficient yield of lymphocytes for CAR-T cell production is feasible also for patients with low peripheral blood counts. Up to 12–15 L blood volume should be processed in patients with absolute lymphocyte counts ≤ 1.0/nL.
Gesehen am 28.07.2020